PENGEMBANGAN VIDEO ANIMASI PEMERIKSAAN GULA DARAH UNTUK MENINGKATKAN PENGETAHUAN USIA PRODUKTIF DI PUSKESMAS NAGRAK - Muhammad Ridwan Al Mufid; Rahmat Sudiyat (Politeknik Kesehatan Kemenkes Bandung, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease with an increasing prevalence, including among the productive-age population. Limited knowledge regarding blood glucose testing is one of the barriers to DM prevention. This study aimed to develop an animated video on blood glucose testing that is engaging, relevant, and effective in improving knowledge. The research used a Research and Development (R&D) design with the Analyze, Design, Development, Implementation, Evaluation (ADDIE) model, involving 44 visitors aged 15–59 years at Nagrak Public Health Center (Puskesmas) selected through accidental sampling. Instruments included a media feasibility questionnaire and a validated, reliable knowledge test (Cronbach’s Alpha = 0.986). Expert validation scored 100% for content and 82.6% for media (highly feasible). Wilcoxon test showed a significant increase in knowledge scores from 42.3 to 52.8 (p = 0.000). Dissemination via YouTube gained 273 views and positive feedback. In conclusion, the animated video effectively improved knowledge and has the potential for broader implementation in health promotion for DM prevention.